2011
DOI: 10.1108/13217341111181078
|View full text |Cite
|
Sign up to set email alerts
|

Cash conversion cycle and firm's performance of Japanese firms

Abstract: Purpose -The purpose of this paper is to investigate the relation between a firm's cash conversion cycle and its profitability. Design/methodology/approach -The relation between the firm's cash conversion cycle and its profitability is examined using dynamic panel data analysis for a sample of Japanese firms for the period from 1990 to 2004. The analysis is applied at the levels of the full sample and divisions of the sample by industry and by size. Findings -A strong negative relation between the length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
103
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 18 publications
16
103
2
7
Order By: Relevance
“…Deloof (2003) stated that for better performance the time duration for collection of receivable should be kept short. Nobanee et al (2004) suggested that for better performance of company inventory must be converted into cash as early as possible. Eljelly (2004) found significantly inverse association and linkage between the profitability and the liquidity represented by the cash conversion cycle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deloof (2003) stated that for better performance the time duration for collection of receivable should be kept short. Nobanee et al (2004) suggested that for better performance of company inventory must be converted into cash as early as possible. Eljelly (2004) found significantly inverse association and linkage between the profitability and the liquidity represented by the cash conversion cycle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karakter keuangan perusahaan yang direpresentasikan dengan 5 (lima) ukuran yaitu: indeks produktifitas, indeks profitabilitas, indeks likuiditas, indeks ukuran perusahaan, dan indeks dividen (Keown et al, 2003;Gill et al, 2010;Nobanee et al, 2011;Al-Shubiri dan Aburumman, 2013;Wiyono dan Mumpuni, 2016). Selanjutnya karakter keuangan yang bagus akan mendorong meningkatnya nilai perusahaan yang diukur dengan price earning ratio (Afza dan Nazir, 2008;Fun dan Basana, 2012;Wu, 2014;Ashvinkumar dan Solanki, 2014).…”
Section: Gambar 1 Rerangka Pikirunclassified
“…Semakin pendek siklus koversi kas, semakin bagus pengaruhnya terhadap karakter keuangan maupun price earning ratio. Karakter keuangan yang dimaksudkan adalah: indeks produktifitas, indeks profitabilitas (Nijam, 2016;Martha dan Januarti, 2013;Karaduman et al, 2011;Khan dan Ali, 2016;Ibe, 2013), indeks likuiditas (Ware, 2015;Lyroudi dan Lazaridis, 2000) indeks ukuran perusahaan, dan indeks dividen (Keown et al, 2003;Gill et al, 2010;Nobanee et al, 2011;Hashemijoo et al, 2012;Wiyono dan Mumpuni, 2016). Sementara itu Price Earning Ratio (PER) adalah rasio yang menggambarkan keuntungan emiten saham (company's earnings) terhadap harga sahamnya (stock price) Geetha dan Swaaminathan (2014), Ozlen (2014 .…”
unclassified
“…The study by Nobanee et al (2011) was reviewed, and it was found that the authors discussed that "[a]s the Japanese business environment is relatively different from that of other top economies of the world, it is interesting to examine whether the characteristics of the Japanese firm might have an effect on their cash conversion cycle and therefore their profitability. Japanese firms' organizational structure is totally different from that of US firms and the rest of the world, after Second World War, "keiretsu" spread into financial institutions in Japan.…”
Section: Payables Management To Return In a Supply Chain Networkmentioning
confidence: 99%
“…For example, Shin and Soenen (1998), as cited by Nobanee et al (2011) used operational measures of profitability such as operating income plus depreciation divided by total assets, and operating income plus depreciation divided by net sales.…”
Section: 8mentioning
confidence: 99%